ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENAGIHAN AKTIF DENGAN SURAT TEGURAN DAN SURAT PAKSA SERTA TERHADAP PENCAIRAN TUNGGAKAN PAJAK DI KPP PRATAMA MALANG SELATAN - Novinia Kristy Viananda (Jurnal Ilmiah Mahasiswa FEB, 2017)
Taxes are the largest source of government revenues required for state financing.  Thus,  the  state  government  need  to  implement  various efforts  to increase the role of taxpayers to optimize tax revenue. This research is conducted to  know  the  effectiveness  and  active contribution of  tax  collection  with Reprimand Letter and Distress Warrant in South Malang Pratama Tax Office in the period 2014-2015 as well as analyze the hindrance that arise. The type of this research is qualitative descriptive. The method of analysis used in this study is statistical descriptive analysis with statistical processing using the formula calculation of effectiveness and contribution, to provide an overview, whether the collection of taxes with Letters of Reprimand and Distress Warrant executed are effective or ineffective, and how its contribution to total government revenues obtained. The research results show that the collection of tax with Reprimand Letter and Distant Warrant in South Malang Pratama Tax Office is not effective and its contribution is very less to total revenue. Thus, South Malang Pratama Tax Office need to do various efforts, with the expectation that implementation of tax collection by Reprimand Letter and Distant Warrant in South Malang Pratama Tax Office in the future become effective and give very good contribution to government revenues.Keywords: effectiveness, tax billing, reprimand letter, distress warrant